A novel biomimetic micro/nano hierarchical interface of titanium enhances adhesion, proliferation and osteogenic differentiation of bone marrow mesenchymal cells - WANG Min; JIANG Nan; ZHU Songsong (口腔疾病防治, 2021)
Objective To design a novel biomimetic micro/nano hierarchical interface on endosseous titanium implants and investigate its effect on the biological activity of bone marrow mesenchymal cells. Methods Electrochemical anodization and spark plasma sintering were used to modify smooth titanium (untreated Ti group) with a microporous trabecular bone-like architecture (micro-Ti group) and TiO2 nanotube architecture (nano-TiO2 group). Additionally, electrochemical anodization was employed to prepare TiO2 nanotubes on microporous trabecular bone-like architectures, which formed a novel biomimetic hierarchical interface (micro/nano-TiO2 group). Four groups of titanium samples were characterized by field emission scanning electron microscopy (SEM), atomic force microscopy (AFM) and contact angle (CA). Bone marrow mesenchymal cells (BMMCs) were seeded on four groups of titanium samples. Scanning electron microscopy (SEM) was employed to observe cell morphology. Cell proliferation was determined by MTT assay. The expression of focal adhesion proteins (F-actin; vinculin; osteocalcin, OCN; osteopontin, OPN) were observed under a confocal laser scanning microscope (CLSM). The mRNA expression levels of osteogenic factors (runt-related transcription factor 2, RUNX2; osteocalcin, OCN; osteopontin, OPN; collagen I, COL I) were assessed by qRT-PCR. Results The micro/nano- TiO2 group featured a hydrophilic surface (CA=9° ± 2.1°). The results of the MTT assay indicated that the relative cell proliferation rates for the nano- TiO2 and micro/nano-TiO2 samples were significantly increased compared with those for the untreated-Ti and micro-Ti samples (P＜0.001) after 5-9 days. The ALP results indicated that the micro/nano-TiO2 sample gained the highest value at 14 days. After 72 h of incubation, the expression of osteocalcin (OCN) and osteopontin (OPN) on micro/nano-TiO2 was the strongest. After 24 h incubation, the expression of F-actin on micro/nano-TiO2 was the strongest. In comparison with untreated-Ti and micro-Ti samples,the mRNA expression levels of all the osteogenic factors (runt-related transcription factor 2, RUNX2; osteocalcin, OCN; osteopontin, OPN; Collagen I, COL I) were markedly increased on the nano-TiO2 and micro/nano-TiO2 samples, the mRNA expression levels of collagen I (COL I) were significantly different between the nano-TiO2 and micro/nano-TiO2 samples versus the untreated-Ti and micro-Ti samples (P＜0.001). Conclusion The novel biomimetic micro/nano hierarchical interface has a positive effect on cell attachment, viability and osteogenic differentiation of bone marrow mesenchymal cells.